Motivasi Petani Karet dalam Melakukan Konversi Perkebunan Karet Menjadi Kelapa Sawit di Kabupaten Sintang - Viero, Agustinus; Dolorosa, Eva; Suharyani, Anita (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Rubber and palm oil are the two largest and leading plantation commodities in West Kalimantan. However, the decline in production and area of rubber plantations continues to occur due to the conversion of rubber commodities to palm oil. This study aims to analyze the motivations that influence rubber farmers in converting rubber plantations to palm oil. The sampling technique in this study was nonprobability sampling with a snowball sampling technique (Snowball Sampling Method). The sample in this study was 100 rubber farmers who converted rubber plantations to palm oil. The analysis tool used was Smart-PLS 3. The results of the study showed that physiological needs, safety needs, the esteem need, self-actualizations had a significant effect on the motivation of rubber farmers to convert rubber plantations to palm oil.